The Relationship of Motivation and Interest of Culinary Students Regarding Entrepreneurial Practices - Prasetya, Rizky Nova; Handajani, Sri (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2024)
This study aims to determine the relationship between the motivation and interest of culinary students regarding entrepreneurial practices. This research is descriptive research with a quantitative approach. The population in this study was class XI students majoring in Culinary at SMK Dharma Wanita Gresik, with as many as 35 students. The data research was collected through questionnaires and observations. The results showed that: (1) there was no positive and significant relationship between motivation towards the entrepreneurial practice. This is proved by the (0.151 0.334) correlation with a significance of 0.386, (2) there is no positive and significant relationship between the interest in entrepreneurship and the entrepreneurial practice. This is proved by the (0.171 0.334) correlation with a significance of 0.326, and (3) there is no positive and significant relationship between the motivation and interest in entrepreneurship towards the entrepreneurial practice. This is proved by the (0.172 0.334) correlation with a significance of 0.618. The degree of relationship between the variables X1 and X2 to Y is very low.